2021
DOI: 10.1002/saj2.20333
|View full text |Cite
|
Sign up to set email alerts
|

Land management effects on wet aggregate stability and carbon content

Abstract: Land management affects soil structure and many other soil properties and processes. Our objectives were to evaluate soil organic C (SOC), aggregate size distribution, aggregate‐associated C, and soil structure as affected by long‐term land management and slope. A chronosequence of 38 on‐farm sites with low to high (5–18%) slopes was selected to evaluate 5–40 yr of management. The sites were classified as business as usual (BAU) cropland (BAU‐Crop), BAU pasture (BAU‐Past), newly established conservation reserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…This CPC aggregate sizes order differs under CT1 and NT+H where microagreggates fraction stored the most SOC (4.5 and 4.4 g kg −1 ), followed by small macroaggregates (3.5 and 2.0 g kg −1 ), silt+clay fraction (2.2 and 1.5 g kg −1 ) and large macroaggregates (0.31 and 0.62 g kg −1 ), respectively. Therefore, in this management, the C sequestration effect of microaggregates was stronger than that of macroaggregates in line with other studies [76,77]. The predominance of SOC in the microaggregates in CT1 and NT+H showed that, under these management strategies, the aggregates-associated SOC had less physical protection, lost macroaggregate integrity and reduced soil binding agents.…”
Section: Soil Organic Carbon Preservation Capacitysupporting
confidence: 85%
“…This CPC aggregate sizes order differs under CT1 and NT+H where microagreggates fraction stored the most SOC (4.5 and 4.4 g kg −1 ), followed by small macroaggregates (3.5 and 2.0 g kg −1 ), silt+clay fraction (2.2 and 1.5 g kg −1 ) and large macroaggregates (0.31 and 0.62 g kg −1 ), respectively. Therefore, in this management, the C sequestration effect of microaggregates was stronger than that of macroaggregates in line with other studies [76,77]. The predominance of SOC in the microaggregates in CT1 and NT+H showed that, under these management strategies, the aggregates-associated SOC had less physical protection, lost macroaggregate integrity and reduced soil binding agents.…”
Section: Soil Organic Carbon Preservation Capacitysupporting
confidence: 85%
“…Lack of yield differences among tillage practices should not be used as a sole basis for choosing a particular type of tillage because there may be other benefits accrued from adopting other tillage practices. For example, studies conducted at the same site found soil organic carbon and aggregate stability to be more substantial in NT plots than in MP plots (Blanco‐Canqui, Mikha et al., 2009) which could be beneficial to enhance soil structural stability and maintain land sustainability (Mikha et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Land survey requires on-site investigation and sampling, collecting data on land attributes, soil samples, etc. [13][14]. Public data sources can utilize public data provided by government agencies, research institutions, or other organizations, such as geographic data, land use data, climate data, etc.…”
Section: Acquisition and Preprocessing Of Land Resource Datamentioning
confidence: 99%